DETERMINING LINGUISTIC IDENTITY OF ETHNIC GROUPS AS THE INFLUENCING FACTOR ON EDUCATIONAL ACTIVITY (CASE STUDY OF REPRESENTATIVES LIVING IN THE SOUTH OF THE TYUMEN REGION) - I. K. Tsalikova; S. V. Pakhotina (Russian State Vocational Pedagogical University, 2018)
Introduction. Nowadays, in the modern world there is a marked tendency towards increasing mobility of the population. The problem of regular complex monitoring of migration processes is caused by the need for assimilation of representatives of the ethnic minorities arriving to the permanent residence to regions of Russia, which neither geographically, nor linguistically are areas with high concentrations of their native ethnic groups. Unfortunately, statistical information on migrants in the majority of regions is limited to the results of national population censuses. In the meantime, the lack of analytical work does not enable to solve effectively a number of essential social problems, including the field of education where teachers often face problems of training of pupils of multinational composition and have to consider a linguistic identity of ethnic minorities.The aim of the present article is to reveal and describe the principles of determination of linguistic identity of ethnic groups according to their influence on activity of subjects of education and educational policy of the region (the case study of the representatives of various ethnic groups, living in the south of the Tyumen Region, the town of Ishim).Methodology and research methods. The study was based on a comparative historical method of investigation. The main research methods involve: contentanalysis of legislative acts and documents; participant and non-participant observation over the migrants' children during individual work on teaching the Russian and English languages; qualitative and quantitative analysis; the survey methods, including the expert questionnaires, conducted by specially developed techniques.Results and scientific novelty. The full linguistic representation of the city with the multinational population is given on the basis of the statistical data obtained from official sources and gained during the empirical research. The language strategies used by migrants are described. The complex of the principles that helps the representatives of various ethnic groups establish the linguistic identity is outlined. Positioning of linguistic self-identity is considered as the factor influencing educational activity of all its subjects. It is noted that the greatest difficulties with linguistic and social assimilation are experienced by migrants' schoolaged children. It is shown how linguistic self-determination of school students and members of their families is related to the quality of children education at school.Practical significance. The research findings have important implications to adjust for the measures undertaken by the government for successful integration of migrants and their children into the ethnic Russian-speaking majority that is significantly important for effective functioning of the educational system.